Enhancing energy harvesting performance and sustainability of cellulose-based triboelectric nanogenerators: Strategies for performance enhancement - Liao, Hongwu; Na, Jongbeom; Zhou, Weiming; Hur, Seungjae; Chien, Monica; Wang, Chong; Wang, Liwei; Yamauchi, Yusuke; Yuan, Zhanhui (Elsevier BV, 2023)
The utilization of triboelectrification and electrostatic inductive coupling to convert mechanical energy into electrical energy has generated significant attention, inspiring the development of triboelectric nanogenerators (TENGs) as a promising solution for energy harvesting. Nevertheless, in the pursuit of material innovation, there is still a significant challenge of achieving an optimal balance between high triboelectric output and environmental sustainability. Among the materials being investigated for TENGs, cellulose has become a strong candidate for its natural abundance, biodegradability, and cost-effectiveness, with numerous studies reporting on its modification. As a result, there is a need for a well-defined classification system for these approaches. This paper provides a detailed description of the working processes and modes of TENG, enhancement techniques for cellulose-based TENG are categorized into three groups: chemical modification, physical doping, and surface morphological modification. The difficulties and opportunities that now face in the development of cellulosebased TENGs are also highlighted. Our research offers valuable information to scientists and engineers who want to use cellulose as a triboelectric material to develop effective and long-lasting TENGs, a crucial step in fulfilling the rising need for renewable energy.